Measurements of the Hydrodynamic and Vibrational Characteristics to Validate Numerical Calculations of the Structure Excitation by Fluid Flow - A. V. Budnikov; E. I. Shmelev; D. A. Kulikov; A. V. Loginov; S. M. Dmitriev; N. A. Pribaturin; P. D. Lobanov; A. S. Suvorov; A. V. Stulenkov (Приборы и методы измерений, 2019)
Structure vibration under the influence of unsteady hydrodynamic forces caused by the flow around their surfaces can adversely affect durability and rupture life. Reducing the adverse effects of hydrodynamic forces is currently possible with the help of linked CFD and vibration calculations. However, for an adequate description of the associated processes one should use calculation models and approaches specific to the hydro-vibration problem. To justify and validate such approaches, an experimental model was developed and a series of structure excitation tests in water flow was carried out.The model comprises two cylinders installed sequentially in water crossflow. Vibration levels, pressure and velocity fluctuations were measured in the tests as a functions of the flow velocity. The application of different non-intrusive measurement techniques was possible due to relatively simple test model construction which may be used for cross-validation and experimental uncertainty quantification.Flow-structure interaction, caused by synchronization effect of the flow separation frequency (or it’s spectral components) and eigenfrequency of cylinder, was analyzed based on simultaneously measured data. The tests performed gave the information about dynamical characteristics of the flow and vibration parameters of cantilevered cylinders. The experimental results are used for identification of required accuracy of hydrodynamic forces calculation by CFD and validation of oneand two-way linked methods for flow excitation frequency calculation.